The impact of public expenditure on economic growth in Syria during the period 1994-2012 - عاقل, سماح; رولا اسماعيل , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Public spending in Syria experiences a decline in its efficiency, the inability to rationalize it, and the failure of economic and financial policies in the face of waste in public spending. The research consists of two main parts, the first one includes a study of the development of public spending in Syria, both current and investment, and the second part includes a study of the development of economic growth in Syria, and how public spending affects the rate of economic growth in Syria. The research concludes that there is an inverse relationship between current public expenditures and economic growth, as an increase in these expenditures leads to an increase in wages and thus an increase in aggregate demand, and in light of the inflexibility of the production system in the Syrian economy, an increase in aggregate demand will lead to an increase in imports or an increase in inflation, which negatively affects the Economic growth. While public investment spending has a positive impact on economic growth in Syria during the studied period. Keywords: investment public expenditures, current public expenditures, economic growth rate.